Structure: Redesign of the “Large Unit” Content in Music Courses—Taking the Overall Teaching of Traditional Music units in Junior High School as an Example - Nan, Jiang (Journal of Research in Vocational Education, 2025)
This paper focuses on the redesign of the “large-unit” content of music courses. In the context of the continuous development of music education, traditional unit teaching has problems such as fragmented content, and the redesign of “large-unit” content has become an inevitable trend. The study deeply analyzes the current status of music course unit teaching and clarifies the need for redesign. Through redesign, we can break the boundaries of knowledge and build a systematic, coherent and in-depth music course system to help students form a complete music cognitive structure and improve their comprehensive music literacy.